Student Learning Innovation Blind Through Approach Solution Case Integrated Audio Based Learning Management System at Islamic University of Makassar - Supriadi, Supriadi; Erniati, Erniati; Nurdiansyah, Erwin; Jumriati, Jumriati; Tumpu, Abu Bakar; S, Herawati Arief; Room, Rusdi; Syukriadi, Dwi (Lembaga Sembilan Tiga Community, 2025)
Study This aiming For developing the Indonesian Language and Literature Education study program FKIPS UIM expands access education for student blind , improve quality service learning For student blind , Improve access , participation and independence student blind operate role in society . The method used in the research using method participatory . The results of study This show that develop RPS problem solving model case audio based for students​ disability specifically student blind Already implemented with good , 2) Has developed audio - based teaching materials for students disability specifically student blind ; 3) Has developed learning media audio based for students​ disability specifically blind students ;4) Have developed evaluation learning audio based for students​ disability especially blind students, and 5) Has developed reporting results Study Program Evaluation education Indonesian language and literature .